(untitled) (REMUNOM, 2025)
For the purpose of reducing existing inocula, as well as preventing subsequent infection and enabling the control of insects and fungi during the early stages of wheat cultivation, seed treatment with agrochemicals is commonly performed. However, the physiological potential of the seeds may be affected by the products incorporated into the treatment solutions. The present study aimed to evaluate the effect of a combination of insecticide (Cruiser Opti®), fungicides (Attic® and Baytan®), biostimulant (Colorseed®), and micronutrients (Macrogreen Micro Booster®) on the vigor and germination capacity of wheat seeds of the TBIO Toruk® and TBIO Sonic® varieties, both immediately after treatment and after a storage period. The trial was conducted in a completely randomized design using a factorial experimental scheme with three factors and four replications. The first factor (cultivar) consisted of two levels. (TBIO Sonic® and TBIO Toruk® cultivars). The second factor (seed treatment) consisted of four levels (0 days of storage without seed treatment, 120 days of storage without seed treatment, 0 days of storage with seed treatment, and 120 days of storage with seed treatment). The third factor (accelerated aging) consisted of two levels (absence and presence of accelerated aging). Although not statistically significant, it was observed that seeds of both cultivars, whether subjected to storage or not, when treated prior to germination, exhibited higher vigor indices and germination potential compared with untreated seeds.